Factors Associated with HIV/AIDS Healthcare Access among PLHIV: A Systematic Review and Meta-Analysis - Nelly Nur Cahya; Adi Nugroho; Musafaah Musafaah; Hardyan Sauqi; Meitria Syahadatina Noor; Roselina Parahiyangan (GLOBAL HEALTH SCIENCE GROUP, 2026)
Access to HIV/AIDS health services remains a major challenge in many developing countries. Factors such as health literacy, insurance coverage, health service availability, and psychosocial barriers influence healthcare utilization among people living with HIV/AIDS (PLHIV). This study aimed to analyze factors associated with access to health services among PLHIV through a systematic review and meta-analysis. A systematic review and meta-analysis were conducted using articles published between 2019–2024 from databases including PubMed, Scopus, ScienceDirect, and Google Scholar. 5094 articles were obtained, of which only 5 articles were used. The meta-analysis showed that PLHIV with good knowledge had significantly better access to healthcare services compared with those with poor knowledge (POR=2.03; 95% CI: 1.19–3.46; p=0.010). Health insurance ownership was also significantly associated with healthcare access (POR=0.83; 95% CI: 0.74–0.93; p=0.002). Narrative synthesis indicated that healthcare accessibility, healthcare worker support, patient perceptions, stigma, and financial barriers strongly influenced viral load monitoring and ART adherence. Knowledge and health insurance ownership are important determinants of healthcare access among PLHIV. Strengthening HIV health literacy, improving healthcare financing systems, and expanding accessible HIV services are essential to improve continuity of care and viral load monitoring.